3D Printing Flexible Sodium‐Ion Microbatteries with Ultrahigh Areal Capacity and Robust Rate Capability. Issue 39 (26th August 2022) - Ma, Jiaxin; Zheng, Shuanghao; Chi, Liping; Liu, Yu; Zhang, Ying; Wang, Kai; Wu, Zhong‐Shuai
Abstract: Rechargeable sodium‐ion microbatteries (NIMBs) constructed using low‐cost and abundant raw materials in planar configuration with both cathode and anode on the same substrate hold promise for powering coplanar microelectronics, but are hindered by the low areal capacity owing to the thin microelectrodes. Here, a prototype of planar and flexible 3D‐printed NIMBs is demonstrated with 3D interconnected conductive thick microelectrodes for ultrahigh areal capacity and boosted rate capability. Rationally optimized 3D printable inks with appropriate viscosities and high conductivity allow the multilayer printing of NIMB microelectrodes reaching a very high thickness of ≈1200 µm while maintaining effective ion and electron‐transfer pathways in them. Consequently, the 3D‐printed NIMBs deliver superior areal capacity of 4.5 mAh cm −2 (2 mA cm −2 ), outperforming the state‐of‐the‐art printed microbatteries. The NIMBs show enhanced rate capability with 3.6 mAh cm −2 at 40 mA cm −2 and robust long‐term cycle life up to 6000 cycles. Furthermore, the planar NIMB microelectrodes, despite the large thickness, exhibit decent mechanical flexibility under various bending conditions. This work opens a new avenue for the construction of high‐performance NIMBs with thick microelectrodes capable of powering flexible microelectronics. Abstract : A prototype of fully 3D‐printed planar flexible sodium‐ion microbatteries is demonstrated with 3D interconnected conductive thick microelectrodes via multilayer printing for ultrahigh areal capacity and robust rate capability, benefiting from the elaborate printable inks and impressive ion/charge‐transfer kinetics.